What has changed in the abdominal anterior wall defects in newborns? 20 years of experience of a tertiary reference hospital - Saraç, Mehmet; Tartar, Tugay; Bakal, Ünal; Aydin, Mustafa; Kazez, Ahmet (Logos Medical Publishing, 2019)
Objective: The aim of this study was to investigate changes of the incidence, complications and mortality rates of patients with anterior abdominal wall defects (AWDs) over the years. Material and Method: Patients who were operated due to anterior AWDs between 1998 and 2017 were evaluated retrospectively. The cases were divided into two groups as cases with omphalocele (OM) and gastroschisis (GS). Then the patients were separated into two subgroups: As operated between January 1998 and December 2007 (Group A), and between December 2017 and January 2008 (Group B). The diagnosis, incidence, prenatal diagnosis (if any), development of sepsis, surgical complications and mortality rates of the patients were recorded. Results: The incidence of Group A patients with OM (n:11, 22%) was 0.2 percent. Two (18.2%) patients were diagnosed during prenatal period. Surgical complications developed in 45.5% (n:5), and sepsis in 18.2 % (n:2) of the patients. Mortality rate in this group was %45.5 (n:5). In Group B (n:24, %48) the incidence of OM was 0.27 percent Prenatal diagnosis was made in 29.2% (n:7) of the cases. Surgical complications developed in 33.3% (n:8), and sepsis in 25% (n:6) of these patients. Mortality rate in this group was 29.2% (n:7). In Group A patients (n:5, 10%), the incidence of GS was 0.089. Twenty percent (n:1) of the patients received prenatal diagnosis Surgical complications developed in 40% (n:2), and sepsis in 40% (n:2) of the patients. Mortality rate was orani 60% (n:3) idi. Its incidence among Group B patients (n:10; 20%) was 0.18 percent. Five (50%) patients were diagnosed during prenatal period Surgical complication developed in 30% (n=3), and sepsis in 50% (n:5) of the patients. Mortality rate in this group was 50% (n:5). Conclusion: The reduction of complications and mortality rates was achieved with the increase of prenatal diagnosis and-the birth of the cases in the centers where they can be treated. © 2019 Logos Medical Publishing. All Rights Reserved.
Yenido?anlarda karin ön duvari defektlerinde neler de?işti? Referans bir hastanenin 20 yillik deneyimi
Keywords: Gastroschisis; Incidence; Mortality; Neonate; Omphalocele